Pengaruh Variasi Dosis Tawas Terhadap Penurunan Kadar Phosphate Air Limbah Rumah Sakit PKU Muhammadiyah Surakarta - PUTRI, OKTAVIANA; , Heru Subaris K, SKM., M.Kes; , Dwi Astuti, SKM., M.Kes (2015)
Liquid waste containing phosphate substances impact on human health .Levels of phosphate test based on the introduction that in doing in PKU Muhammadiyah Surakarta Hospital of 5,7 mg/l, these results more than raw waste water quality. One way that can be done is with the process of coagulation using koagulan alum. The purpose of this research is aware of the influence of alum doses of variations on the decline in levels of phosphate in PKU Muhammadiyah Surakarta Hospital. The type of research true experiment with pre-post test with control design. The location of research at PKU Muhammadiyah Surakarta Hospital. Processing using variations of a dose of alum 0.25 gr/l , 0.5 gr/l and 0.75 gr/l with a method of slow manual stirring 100rpm 10 minutes .The results of average the decline in levels of phosphate every variation namely dosage 67,03 %; 91,98 %; and 99,82 % .The statistics used is Shapiro-Wilk and One-Way Anova. Based on the analysis with the use of one-way anova in the treatment group and the control for levels of phosphate < 0.01, which means that there is variation doses influence alum to a decrease in levels of phosphate. Suggested in other researchers to conduct a similar study using koagulan other kinds for reprocessing with the methods of coagulation with other parameters such as BOD, COD or other metal.